1988
DOI: 10.1177/107110078800900303
|View full text |Cite
|
Sign up to set email alerts
|

Objective Evaluation of Insert Material for Diabetic and Athletic Footwear

Abstract: Five of the most commonly used materials for shoe inserts (soft Plastazote, medium Pelite, PPT, Spenco, and Sorbothane) were objectively evaluated in the laboratory to characterize their behavior in the following three specific functions that correspond to clinical use: (1) the effect on the materials of repeated compression. (2) the effect of a combination of repetitive shear and compression. (3) the force-distribution (force-attenuation) properties of these materials, both when new and after repeated compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 2 publications
1
44
0
2
Order By: Relevance
“…The surfaces were chosen such that the stiffness of two surfaces, PU and SS25, were similar and the percentage of energy loss of SS60 and SS25 were similar as these two physical properties have been shown to improve comfort and to reduce impact loads and injuries (Basford and Smith, 1988;Brodsky et al, 1988;Cook et al, 1985;Schwellnus et al, 1990). The laser scans and the analyses related to the castings clearly showed that mid-foot plantar shapes were significantly different, even though the rear-foot and forefoot were fixed and the same among the three surfaces.…”
Section: Surface Type Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surfaces were chosen such that the stiffness of two surfaces, PU and SS25, were similar and the percentage of energy loss of SS60 and SS25 were similar as these two physical properties have been shown to improve comfort and to reduce impact loads and injuries (Basford and Smith, 1988;Brodsky et al, 1988;Cook et al, 1985;Schwellnus et al, 1990). The laser scans and the analyses related to the castings clearly showed that mid-foot plantar shapes were significantly different, even though the rear-foot and forefoot were fixed and the same among the three surfaces.…”
Section: Surface Type Effectsmentioning
confidence: 99%
“…Some studies have found that neoprene insoles reduce transmitted forces better than viscoelastic insoles (Brodsky et al, 1988). Cook et al (1985) attributed the increase in risk of stress fractures to a loss of mechanical support or the shock-absorbing properties of the midsole of footwear.…”
mentioning
confidence: 99%
“…This may suggest that differences in the training environments may influence the results. Future studies should better characterize the training environment as well as degree of shock absorbency, durability, and other important characterisfics of insoles (22). Soldiers In the U.S. Army have used running shoes for physical training since the early 19B0s.…”
Section: (2) Equipment Modification Strategiesmentioning
confidence: 99%
“…Incorrect support may lead to injuries in the long term. This is even worse when wearers suffer from certain illnesses, such as diabetes, where correct pressure distribution is critical to prevent ulceration [3]. There are certain essential aspects characterising an insole.…”
Section: Introductionmentioning
confidence: 99%